The Influence of Tourism Marketing, Authenticity, and Tourism Experiences on Tourist Satisfaction and Revisit Intention at Jamus Agrotourism Ngawi - Raissalma Queena Alhilwa; Azizah, Nurul (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of tourism marketing, authenticity, and tourism experience on tourist satisfaction and revisit intention at Agrowisata Jamus Ngawi. The purpose of this research is to identify the direct and indirect relationships among the variables. The study used a quantitative approach with 155 respondents and SmartPLS analysis. The results show that all variables have a positive and significant effect on tourist satisfaction and revisit intention, with tourism experience as the most dominant factor. These findings highlight the importance of effective marketing strategies, destination authenticity, and quality tourism experiences in enhancing tourist satisfaction and revisit intention.